Charles Baudelaire: A Study - Symons, Arthur, 1865-1945 (Salt Lake City, UT : Project Gutenberg, 2015)
"Charles Baudelaire: A Study" by Arthur Symons is a critical examination of the life and work of the esteemed French poet, written in the early 20th century. The book delves into Baudelaire's complex personality, his artistic genius, and the themes he explored in his influential poetry, particularly in "Les Fleurs du Mal." It aims to unravel the intricacies of Baudelaire's thoughts and feelings about life, art, love, and the human condition, offering insights into the paradoxes that defined his existence. The opening of the study sets the tone for an in-depth analysis of Baudelaire's artistic approach and the dualities that permeate his work. Symons discusses how Baudelaire's genius manifests not through direct assertions but rather through subtle implications, often colored by his personal experiences and observations of society. He highlights Baudelaire's struggles with love and despair, particularly relating to his tumultuous relationships, most notably with Jeanne Duval. The narrative also introduces a broader discussion on the aesthetics of Baudelaire's writing, juxtaposing his sensual yet morbid sensibility against the backdrop of a world fraught with contradictions$1 (Ba reflection on the allure and repulsion of beauty amid darkness. (This is an automatically generated summary.)s
Release date is 2015-11-19
Produced by Marc D'Hooghe (Images generpously made available by the Internet Archive.)
Keywords: Baudelaire, Charles, 1821-1867; Poets, French -- 19th century -- Biography